On nonlinear thermal buckling analysis of cylindrical shells. (October 2015) - Alijani, A.; Darvizeh, M.; Darvizeh, A.; Ansari, R.
Abstract: In this article, the nonlinear buckling behavior of imperfect cylinders made of isotropic, composite and functionally graded materials is studied. A continuum-based semi-analytical finite element formulation is introduced to study the nonlinear behavior of cylinders under thermal loads. A method is proposed to implement the initial geometric imperfection of the cylinder by transformation of structure due to deformation gradients. The influences of geometrical parameters, different materials and imperfection factors are investigated on pre- and post-buckling paths. A comparison is made between the classical von Kármán-based and continuum-based approaches to ensure the validation of the results and to study the applicability of the von-Kármán approximation. Highlights: A nonlinear semi-analytical finite element method according to continuum-based approach is developed for cylindrical shells under thermal buckling. The several applied comparisons between two approaches 'continuum-based approach and classical approach' survey their results. A method is proposed to implement the initial geometric imperfection of the cylinder by transformation of structure due to deformation gradients. The nonlinear buckling paths are not very sensitive to the length of cylindrical shells however; these buckling paths are greatly affected by the radius of them.